Ear wound regeneration in the African spiny mouse Acomys cahirinus - Santos Matias, Dino (2016)
While regeneration occurs in a number of taxonomic groups across the Metazoa, there are very few reports of regeneration in mammals, which generally respond to wounding with fibrotic scarring rather than regeneration. A recent report described skin shedding, skin regeneration and extensive ear punch closure in two rodent species, Acomys kempi and Acomys percivali. We examined these striking results by testing the capacity for regeneration of a third species, Acomys cahirinus, and found a remarkable capacity to repair full thickness circular punches in the ear pinna. Four-millimeter-diameter wounds closed completely in 2 months in 100% of ear punches tested. Histology showed extensive formation of elastic cartilage, adipose tissue, dermis, epidermis and abundant hair follicles in the repaired region. Furthermore, we demonstrated abundant angiogenesis and unequivocal presence of both muscle and nerve fibers in the reconstituted region; in contrast, similar wounds in C57BL/6 mice simply healed the borders of the cut by fibrotic scarring. Our results confirm the regenerative capabilities of Acomys, and suggest this model merits further attention.